Revista Saúde.Com um elo de comunicação entre os profissionais de saúde - Sales, Zenilda Nogueira; Boery, Rita Narriman Silva Oliveira (Saúde.com, 2017)
Revista Saúde.Com um elo de comunicação entre os profissionais de saúde